SURVEY TINGKAT KEBUGARAN JASMANI - suriah hanafi suriah; Ikadarny Ikadarny (Jurnal Speed (Sport, Physical Education, Empowerment), 2023)
This study aims to determine the level of physical fitness of SMA YP PGRI 1 Makassar students. This research is descriptive quantitative. The method used is a survey with data collection techniques using tests and measurements of the Indonesian Physical Fitness Level (TKJI) aged 16-19 years. The subjects of this study were 30 students of SMA YP PGRI 1 Makassar. Data analysis techniques use descriptive analysis as outlined in the form of percentages. Based on the results of the research and discussion, it was obtained that the results of the physical fitness level of SMA YP PGRI 1 Makassar students were mostly in the very good category, there were 0 males (0%), 6 males (20%) in the good category, 24 males ( 80%) in the medium category. , 0 boys (0%) in the less category, and 0 boys (0%) in the very lacking category. The results of this study can be concluded that the level of physical fitness of SMA YP PGRI 1 Makassar students is in the moderate category.